Stereoselective Synthesis of Drugs and Natural Products 2013
DOI: 10.1002/9781118596784.ssd041
|View full text |Cite
|
Sign up to set email alerts
|

Cycloadditions with StereoselectiveCNBond Formation in Total Syntheses

Abstract: Cycloadditions reactions are very efficient tools for the constructions of multiple bonds in one step and are therefore methods of choice for the total synthesis of natural products and drugs. The use of a terminal nitrogen containing partner allows for the stereoselective formations of a CN bond. Because of the vast number of nitrogen containing compounds available, this field has found a widespread interest in total synthesis. This chapter will cover the cycloadditions in which a CN bond is formed. It will… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 111 publications
(73 reference statements)
0
1
0
Order By: Relevance
“…In this work, it is shown that highly substituted oxazoles and aminothiazoles could be accessed directly from the reaction of substituted α-azidochalcones with potassium thiocyanate. Thiocyanate is a known ambident reagent with two potential sites of attack, enabling the selective and efficient construction of C-C and C-N bonds towards biologically important heterocyclic skeletons [62][63][64].…”
Section: Introductionmentioning
confidence: 99%
“…In this work, it is shown that highly substituted oxazoles and aminothiazoles could be accessed directly from the reaction of substituted α-azidochalcones with potassium thiocyanate. Thiocyanate is a known ambident reagent with two potential sites of attack, enabling the selective and efficient construction of C-C and C-N bonds towards biologically important heterocyclic skeletons [62][63][64].…”
Section: Introductionmentioning
confidence: 99%